Endoscopic and immunohistochemical aspects in an inverted papilloma with unilateral total obstruction of the nasal fossa - Irina Enache; Florin Anghelina; Mircea-Sorin Ciolofan; Carmen Aurelia Mogoantă; Alex Emilian Stepan; Ioana-Cristina Vîlcea; Cosmin Vasile Obleagă; Andrei Osman (Journal of Mind and Medical Sciences, 2024)
An inverted papilloma is a medical condition in which epithelial cells placed on the surface grow in depth into the underlying supporting tissue. The case of a 68-year-old man with a 6-month history of right-sided complete nasal obstruction, who was referred to the ENT Department of our hospital, is presented. The associated symptoms were represented by repeated epistaxis, rhinorrhea and anosmia. From a clinical point of view, a polypous reddish-gray irregular mass, with cauliflower-like appearance, has been described. The formation was friable, richly vascularized, and with minor bleeding on light touch. The patient was diagnosed with inverted papilloma which was treated by endoscopic surgery. By analyzing the clinical, histochemical and immunohistochemical aspects of this case, the cause of tumor growth and its potential for malignant transformation were established. Many particularities are presented in this article: increased regional aggressiveness, its ethmoidal sinus origin, specific symptomatology, paraclinical examinations, all of which were useful in choosing a customized therapy and follow-up program.